(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This research aims to clarify the jurisprudential rulings related to the guarantee of damages resulting from the operation of autonomous vehicles, as they are a contemporary phenomenon imposed by technological progress. The researcher addresses the various jurisprudential adaptations of this type of vehicle, in terms of eligibility and liability, with a detailed study of the reasons and conditions of the guarantee, and the position of responsibility between the owner, the programmer, and the manufacturer. The study concludes that the guarantee falls primarily on the vehicle owner, as the possessor and beneficiary, with the possibility of recourse against the actual perpetrator, in accordance with general jurisprudential rules such as "loss is rewarded" and "harm is removed." The research also discusses the experience of the Emirate of Dubai as a legislative model for regulating the guarantee of these vehicles, placing the possessor—the operator and owner of the vehicle—as the primary responsibility for the guarantee. The research highlights the urgent need for collective jurisprudential effort capable of keeping pace with this rapid technological transformation and regulating its developments in accordance with the objectives of Islamic Sharia.